2014
DOI: 10.1186/s40411-014-0007-5
|View full text |Cite
|
Sign up to set email alerts
|

Towards guidelines for building a business case and gathering evidence of software reference architectures in industry

Abstract: Background: Software reference architectures are becoming widely adopted by organizations that need to support the design and maintenance of software applications of a shared domain. For organizations that plan to adopt this architecture-centric approach, it becomes fundamental to know the return on investment and to understand how software reference architectures are designed, maintained, and used. Unfortunately, there is little evidence-based support to help organizations with these challenges. Methods: We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…However, we remark that there exist organizations with similar contexts to AUTOSAR that could benefit from the results of this survey [18]. As Seddon et al suggests: "if the forces within an organization that drove observed behavior are likely to exist in other organizations, it is likely that those other organizations, too, will exhibit similar behavior" [21].…”
Section: External Validitymentioning
confidence: 92%
“…However, we remark that there exist organizations with similar contexts to AUTOSAR that could benefit from the results of this survey [18]. As Seddon et al suggests: "if the forces within an organization that drove observed behavior are likely to exist in other organizations, it is likely that those other organizations, too, will exhibit similar behavior" [21].…”
Section: External Validitymentioning
confidence: 92%
“…Also, vendors of the SRA are more likely to also be the provider that develops the applications, e.g., "once you define the SRA for a client organization, you have more options of developing applications on top of that SRA, since you know it" [H]. For this reason, the use of reference models is becoming popular among SRA vendors [9]. Table VIII.…”
Section: The Use Of a Reference Model A Confounding Factormentioning
confidence: 99%
“…We recognize that our results cannot be generalized to other organizations without further work. However, we claim that our study can serve as a basis for other similar organizations to study their SRA's benefits and drawbacks [9]. Other IT consulting firms that could be considered to some extent similar to everis are, for instance, Accenture [41] and Capgemini [42], as they use an industry-specific reference model to provide support to their clients to adopt SRAs, and they have similar professional roles to perform the associated tasks (see Fig.…”
Section: Limitations Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It aggregates knowledge about how to design software architectures of systems of a given application domain (Bass, 2013;Nakagawa et al, 2011). It includes domain business rules, standards and legislation, software and hardware elements, architectural styles and patterns, and best practices of software development in that domain, among other elements (Angelov et al, 2012;Martínez-Fernández et al, 2014;Nakagawa et al, 2011). Hence, the main purpose of reference architectures is to serve as a guide for the development, standardization, and evolution of systems (Nakagawa et al, 2014;Yimam and Fernandez, 2016;Martínez-Fernández et al, 2017).…”
Section: Introductionmentioning
confidence: 99%